1998
DOI: 10.1146/annurev.soc.24.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentalism et al: Conservative Protestants in America

Abstract: Since the rise of the religious right, scholars have become increasingly interested in studying conservative Protestantism. Not only do conservative Protestants (CPs) make up at least a quarter of the US population; they differ from many Americans in gender-role attitudes, childrearing styles, political orientation, and other ways as well. In fact, religious factors often predict people's political views better than do either class or gender, even though the latter two have received far more attention in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
300
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(310 citation statements)
references
References 78 publications
5
300
1
4
Order By: Relevance
“…Hood et al (2005) and Woodberry and Smith (1998) detail how conservative groups associated with the Social Gospel movement withdrew from society in the 1940s and eventually formed branches currently classified as fundamentalist (Hood et al 2005) and Evangelical (Hubbard 1991), with a defining characteristic of both groups being the importance of the proper interpretation of the Christian Bible. Traditionalist factions within the evangelical movement rejected the progressivism of the Social Gospel (Midgley 1990).…”
Section: Alternative Theoriesmentioning
confidence: 99%
“…Hood et al (2005) and Woodberry and Smith (1998) detail how conservative groups associated with the Social Gospel movement withdrew from society in the 1940s and eventually formed branches currently classified as fundamentalist (Hood et al 2005) and Evangelical (Hubbard 1991), with a defining characteristic of both groups being the importance of the proper interpretation of the Christian Bible. Traditionalist factions within the evangelical movement rejected the progressivism of the Social Gospel (Midgley 1990).…”
Section: Alternative Theoriesmentioning
confidence: 99%
“…Scholars of religious fundamentalism count belief in scriptural inerrancy and literalism as key identifiers of fundamentalism (Almond et al, 1995;Hood et al, 2005). Survey researchers frequently use literal interpretation of the Bible as a measure of Christian fundamentalist orientation (Jelen et al, 1990), with variation in biblical literalism found within both traditionally conservative and liberal denominations (Village, 2005;Woodberry and Smith, 1998). Consistent with previous literature (e.g., Hoffmann and Bartkowski, 2008), biblical literalism is understood in this study as taking everything in the Bible as the literal word of God (as opposed to non-literalists who do not take some biblical passages literally, word-for-word).…”
Section: Biblical Literalismmentioning
confidence: 99%
“…Notably, this research shows that conservative Protestants (CPs) are dramatically overrepresented in the bottom of the wealth distribution-particularly on measures of financial asset ownership-independent of family background (Keister 2003a(Keister , 2005. CPs are members of churches with relatively traditional religious beliefs who accept the Bible as the inerrant word of God, value personal conversion experiences, and emphasize the importance of the Christian faith to social issues (Sherkat and Ellison 1999;Woodberry and Smith 1998). Some of the larger and more widelyrecognized CP denominations are Assembly of God, Baptist, Churches of Christ, Church of God in Christ, Nazarene, and Pentecostal.…”
mentioning
confidence: 92%
“…Author's estimates are from the Survey of Consumer Finances. 3 Conservative Protestant denominations are sometimes called "Evangelical," but in reality Evangelicals are a subset of CPs (Smith 2000;Woodberry and Smith 1998). for this group may inform understanding of more general patterns in wealth distribution.…”
mentioning
confidence: 99%